Feasibility study for the implementation of a food and beverage company aimed at the service of initial training educational establishments. - Méndez Bravo, Manuel Alberto; Bayas Córdova , Yadira Estefanía; Manotoa Reyes, Marco Gabriel (Ingeniería Química y Desarrollo, 2024)
Children are fundamental to any society because of the love they receive at home. Agencies such as UNICEF work to ensure the well-being of children. In Ecuador, where this study is being conducted, children's rights are a priority. A key element for their development is adequate nutrition. Despite the efforts of the State and parents, Ecuador suffers from high levels of child malnutrition, possibly associated with poor nutrition in school-age children. This is due to parents' lack of time to prepare balanced meals, lack of knowledge about a healthy diet, or economic limitations. This study will evaluate the feasibility of creating a catering company to feed the Centro de Educación Inicial Santa Teresa de Jesús in Durán, Guayas. The objective is to improve the nutrition of the children through meals that allow for optimal growth. Scientific advances have shown that certain foods are related to health problems. This generates greater awareness, especially in children who need adequate nutrition for their development. The State and parents must guarantee children's food security.
Keywords: Balanced diet; Nutrition; Catering; Initial education; Entrepreneurship